Cardiac Response Dynamics in Newly Diagnosed Light-Chain Amyloidosis Patients With Early and High-Quality Hematologic Response - Cheng-yang Xu, MD; Ai Guan, MD; Lu Zhang, MD; Zhuang Tian, MD; Dao-bin Zhou, MD; Kai-ni Shen, MD; Jian Li, MD (JACC: Asia)
Background: The goal of hematological response has been well established in the treatment of systemic light chain amyloidosis. However, the pattern of cardiac response remains unknown. Objectives: This study was designed to investigate the cardiac response dynamics in patients with an early and high-quality hematological response. Methods: This retrospective study included newly diagnosed patients who achieved a hematological response of very good partial response or better within 3 months after treatment beginning. Four cardiac response criteria were tested at fixed time points (3, 6, 12, and 24 months after therapy initiation): cardiac complete response, cardiac very good partial response, cardiac partial response (carPR), and cardiac no response. Results: A total of 201 patients were included, with the median follow-up 37.0 months (Q1-Q3: 18.0-56.5 months). The cardiac response reached a plateau at 24 months, while cardiac complete response, cardiac very good partial response, and carPR were achieved in 21.4% (28 of 131), 38.9% (51 of 131), and 20.6% (27 of 131) of the patients, respectively. At every fixed time point within 12 months after treatment initiation, patients who achieved a carPR or better consistently had better survival than did those who did not. At 3 months, an NT-proBNP concentration ≥3,716 pg/mL was the only factor associated with a decreased likelihood of achieving a carPR within 12 months (OR: 0.269; 95% CI: 0.137-0.512; P < 0.001). Conclusions: This study emphasizes the importance of monitoring cardiac response dynamics for disease surveillance. In patients who achieve early and high-quality hematological response, it is important to achieve carPR within 12 months.